Development and Effectiveness Test of a Gamification-Based Mathematics Learning Media Integrated With Vocational Problems on Numeracy Literacy Ability - Solehudin, Seva Zidan; Maharani, Anggita; Nasir, H.Fuad (Universitas Islam Negeri Raden Intan Lampung, 2026)
Despite the increasing adoption of digital learning platforms in vocational education, mathematics instruction often remains procedural and provides limited opportunities for students to develop contextual numeracy skills relevant to workplace situations. This study aimed to develop and examine the preliminary effectiveness of a gamification-based mathematics learning medium using Quizizz that integrates vocational problems with the Assessment of Minimum Competency (AKM) numeracy processes of formulating, employing, and interpreting. The study employed a Research and Development approach using the ADDIE model. A needs analysis involved 48 Grade X vocational students in the Office Management and Business Services program, while the implementation stage involved 29 students. The developed product was validated by two mathematics education lecturers and two mathematics teachers. Data were analyzed using percentage analysis, normalized gain, and a paired-samples t-test procedure. The validation results categorized the learning medium as highly valid after revisions to instructional clarity, language, illustrations, and visual presentation. Students' mean numeracy score increased from 46.36 on the pretest to 61.69 on the posttest, with a mean N-Gain of 0.23 (minimum = −0.38, maximum = 0.78, SD = 0.32), indicating modest overall improvement accompanied by considerable variation in individual learning gains. These findings provide preliminary evidence that integrating vocational contexts with AKM-oriented gamification offers a valid supplementary environment for contextual numeracy practice. The study contributes to the growing literature on context-sensitive digital mathematics learning by demonstrating how vocational problem contexts and AKM numeracy processes can be integrated within a gamified instructional design while highlighting the need for sustained implementation to achieve stronger learning outcomes.